47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-1069
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Small Scale Coaxial Rotor Aerodynamics in Hover

Abstract: In this work, a compressible Reynolds-Averaged Navier Stokes (RANS) solver is extended to investigate the aerodynamics of a micro-scale coaxial rotor configuration in hover. This required the following modifications to the solver: implementation of a time-accurate low Mach preconditioner, implementation of a sliding mesh interface boundary condition, improvements in the grid connec-tivity and parallelization of the code. First, an extensive validation study on the prediction capability of the solver is perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…Although choosing non-inertial over inertial reference frame has significant advantages in hover calculations [43,44], it can have noticeable impact on solution convergence even in forward flight calculations. One additional advantage of solving the equations in a rotating reference frame is that the grid metrics need to be calculated only once at the start of the solution process.…”
Section: Equations In a Rotating Reference Framementioning
confidence: 99%
See 2 more Smart Citations
“…Although choosing non-inertial over inertial reference frame has significant advantages in hover calculations [43,44], it can have noticeable impact on solution convergence even in forward flight calculations. One additional advantage of solving the equations in a rotating reference frame is that the grid metrics need to be calculated only once at the start of the solution process.…”
Section: Equations In a Rotating Reference Framementioning
confidence: 99%
“…Hole cutting is a byproduct of this process of cell selection. A more detailed description of the workings of the IHC algorithm can be found in [44,62]. …”
Section: Overset Mesh Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, understanding the flow beneath the rotor is necessary to understand how and when sediment is uplifted. Most studies of rotors in ground effect have focused on how rotor performance is affected by near-ground operation [17][18][19][20][21][22][23][24][25][26][27][28]. Some recent studies, however, have provided insight into the detailed flow structures found in the rotor flow near the ground [16,[29][30][31][32][33][34][35][36].…”
Section: Fluid Mechanicsmentioning
confidence: 99%
“…The H/D ratio is used as a non-dimensional figure to enable comparison of multiple systems across a range of scales.  Propeller Pitch -The propellers used in the co-axial tests are fixed pitch, but unlike full-scale rotor blades that have an almost uniform pitch throughout the diameter due the design preference of a symmetrical blade section [6]; the test propellers have a varying pitch.…”
Section: Testing Variablesmentioning
confidence: 99%